Impact of Warfarin on Atrial-Fibrillation Outcomes Related to Economic Consumption Patterns: Hospitalization, Cost, and Mortality may be Predictable and Modifiable at the Population Level. Issue 9 (September 2016) - Kim, Michael; Cai, Qiang; Xu, Liou; Puckrein, Gary
Abstract Introduction Warfarin reduces atrial fibrillation (AF)-related strokes and may impact mortality, hospitalizations, and costs. This study investigated the possibility that patterns of warfarin consumption are associated with the frequency of acute events. Methods Annual cost profiles of 9.2 million Medicare beneficiaries with AF were analyzed to identify patterns of benefits consumption from 2000 through 2010. Beneficiaries were divided into five consumption clusters based upon their annual cost profiles, ranging from crisis consumers at the high end to low consumers. Resource-utilization patterns and outcome differences were calculated between AF beneficiaries who received warfarin and those who did not. Propensity score-matched analysis was performed to reduce selection bias. Results The annual percentages of beneficiaries and expenditures that differentiated each cluster showed stable patterns. Warfarin use influenced consumption patterns and outcomes. The most important financial difference between higher and lower consumers was inpatient cost. AF beneficiaries on warfarin had lower annual cost profiles and had a higher propensity to persist in or migrate to consumption clusters with comparatively small reimbursement claims and lower hospitalization risks. AF beneficiaries not on warfarin had higher cost and mortality. Conclusions These data signal that a nontrivial portion of acute events (hospitalization and mortality) are amenable to medical intervention (warfarin). When acute events are amenable to medical intervention and occur at a higher frequency because guidelines have not been applied evenly across affected populations, it is appropriate to define those occurrences as disparities associated with systemic failure in evidence-based medicine. Quality-improvement initiatives that reduce therapeutic disparities may result in lower cost and improved outcomes. Funding No funding or sponsorship was received for this study or publication of this article.